1981
DOI: 10.1046/j.1537-2995.1981.21281178152.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Storage: An Assessment of the Requirements for Plasma and Oxygen

Abstract: Platelets from several units of plasma were pooled, and then resuspended either as platelet concentrate (PC) (60 ml) or as platelet rich plasma (PRP) (220 ml) and followed during 72 hours of storage at 22 C. Aggregation, pH, and hypotonic shock response are better maintained in the larger volume of plasma. However the decreased pH and function in the PC is not the result of lactate production. While the relative concentration, expressed in mg/dl, is higher in the PC, the absolute production per platelet and, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
6
1

Year Published

1982
1982
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 11 publications
5
6
1
Order By: Relevance
“…It is known that mitochondrial metabolism can be very sub stantial in platelets [12]. The data presented in this report does not support the recent suggestion that oxidative metabolism is of minimal importance in preventing in creased lactate formation during platelet concentrate storage [11],…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…It is known that mitochondrial metabolism can be very sub stantial in platelets [12]. The data presented in this report does not support the recent suggestion that oxidative metabolism is of minimal importance in preventing in creased lactate formation during platelet concentrate storage [11],…”
Section: Discussioncontrasting
confidence: 96%
“…Our data empha sizes that pC02 levels overall are closely related to the pH of the plasma of a platelet concentrate. The association in stored plate lets between pC02 and pH levels has also been described in another recent report [11]. The pC02 values determined for concen trates stored for 24 h (table II) are somewhat higher than those reported in one study [1] but similar to those reported in a second study [13].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…lower pH, higher lactate) already suggested by previous investiga tions by ourselves [5,6,12,13] and others [1,3,4] (tables for all measured responses (table IV), although only the change in serotonin uptake from 80 to 59% was statisti cally significant (p<0.001).…”
Section: Resultssupporting
confidence: 51%
“…
In their recent paper, Högman et al [1] have shown that when red cells were kept in an anaerobic environ ment in the presence of nitrogen, the red cell ATP and adenylate energy charge were significantly better main tained than when red cells were stored in an aerobic environment.They also reported impaired posttransfusion survival and higher spontaneous hemolysis when red cells were stored in some of the newer more permeable plastics rather than traditional polyvinyl chloride (PVC) bags.We had earlier reported similar effects during storage of platelets with impaired in vitro function when platelets were kept in an enriched aerobic environment in which additional oxygen was either added to the storage bag or present in a high concentration in the storage environ ment [2]. In contrast, platelets kept in a nitrogen environ ment -as the red cells in the experiment of Hogman et al

[1] -showed a better in vitro function at all periods of storage.

…”
mentioning
confidence: 65%